The prophet and the age of the Caliphates : the Islamic Near East from the sixth to the eleventh century - Kennedy, Hugh (Hugh N.) (Abingdon, Oxon; New York, NY : Routledge, Taylor & Francis Group, 2023)
'The Prophet and the Age of Caliphates is an accessible history of the Near East from c. 600-1050 AD, the period in which Islamic society was formed. Beginning with the life of Muhammad and the birth of Islam, Hugh Kennedy goes on to explore the great Arab conquests of the seventh century and the golden age of the Umayyad and Abbasid caliphates when the world of Islam was politically and culturally far more developed than the West. The arrival of the Seljuk Turks and the period of political fragmentation which followed shattered this early unity, never to be recovered. This new edition is fully updated to take into account the considerable amount of new research on early Islam, and coverage of eastern Iran, Central Asia and dynasties like the Samanids and Ghaznevids has been expanded. There is also an entirely new chapter on economic history. Based on extensive reading of the original Arabic sources, Kennedy breaks away from the Orientalist tradition of seeing early Islamic history as a series of ephemeral rulers and pointless battles by drawing attention to underlying long term social and economic processes. The Prophet and the Age of Caliphates deals with issues of continuing and increasing relevance in the twenty-first century, when it is, perhaps, more important than ever to understand the early development of the Islamic world. Students and scholars of early Islamic history will find this book a clear, informative and readable introduction to the subject'--
Includes bibliographical references and index.
Buku bacaan asas Fakulti Pengajian Islam sesi 2022/2023.
Keywords: Islamic Empire -- History -- 622-661.; Islamic Empire -- History -- 661-750.; Islamic Empire -- History -- 750-1258.